Hubungan Penyakit Diabetes Melitus dan Penggunaan Antidiabetes terhadap Rekurensi pada Pasien Kanker Payudara - Fitri Wulandari; Kartika Widayati; Fita Rahmawati (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Breast cancer is the cancer with the most prevalence of 43.3% and the mortality rate that reaches 12.9%. The prognosis of breast cancer can be affected by diabetes mellitus (DM), so that efforts to control DM through antidiabetic therapy are very necessary, but antidiabetic therapy is also reported to be associated with the prognosis of breast cancer. The purpose of this study was to determine the relationship of diabetes and antidiabetic use to recurrence in breast cancer patients. This study used a retrospective cohort design, involving 176 female non-metastatic breast cancer patients who received chemotherapy, consisting of 88 patients with DM and 88 non-DM patients. The exposures in the study were diabetes mellitus and the types of antidiabetic drugs (metformin and non metformin based therapy), while the study output was the recurrence of breast cancer. The research data was obtained from the patient’s medical records at RSUP Dr. Sardjito Yogyakarta. Research analysis used Chi-square, Kaplan Meier method and Cox-regression to estimate Hazard Ratio with 95% confidence interval. The results showed DM in breast cancer patients was associated with increased the risk of recurrence (HR 2,458; 95% CI 1,571-3,846, log rank test P=0,000), while the use of antidiabetic types (metformin and nonmetformin) to control DM in breast cancer patients was not associated with the risk of recurrence (HR 1.391; 95% CI 0.816 - 2.370, log rank test P=0.210). Further research is warranted by monitoring blood glucose levels regularly.